The gentleman's guide to vice and virtue - Lee, Mackenzi (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2017)
Vowing to make his yearlong escapade across Europe his last hurrah before taking over the family estate, Henry "Monty" Montague and his best friend Percy find themselves in the middle of a dangerous manhunt involving pirates and highwaymen.